The crystal structure of (tris(2-benzimidazolylmethyl)amine)-benzoato-copper(II) perchlorate monohydrate, CuC 31 H 28 N 7 O 7 Cl - Ji Li; Mingzhi Miao (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
Abstract CuC 31 H 28 N 7 O 7 Cl, triclinic, P 1 ‾ $P\overline{1}$ (no. 2), a = 10.1386(6) Å, b = 12.1155(8) Å, c = 14.1972(8) Å, α = 100.297(2)°, β = 98.411(2)°, γ = 112.744(2)°, V = 1536.78(16) Å 3 , Z = 2, R gt ( F ) = 0.0613, wR ref ( F 2 ) = 0.1519, T = 250(2) K.